Cars Diagnostic on a Photochemical Reactor for IR Laser Induced Production of Si and Si3N4 Powders. Issue 1 (1991) - Fantoni, R.; Bijnen, F.; Djurić, N.; Piccirillo, S.
Abstract : In a flow reactor a low power (up to 50 W) CW CO2 laser tuned at 944, 19 cm −1 has been focussed in order to produce Si and Si3 N4 ultrafine powders from SiH4 and SiH4 /NH3 mixtures. Among possible on-line optical diagnostics, two different CARS techniques have been used to monitor the excitation process and to measure average reaction temperatures in collinear geometry. In broad-band CARS at low resolution (≈6.0 cm −1 ) the reactant temperature is measured from the attenuation of the corresponding integrated peak intensity below and at the dissociation threshold. In narrow-band experiments the temperature reached by the dissociating reactants below and above the threshold is inferred from the spectral shape (measured with 0.2 cm −1 resolution) of the envelope of rovibrational CARS transitions involved. Results obtained at the threshold for SiH4 dissociation are in agreement with previous data on gas-phase pyrolysis in a thermal process. For the SiH4 /NH3 reaction the difficulty in obtaining stoichiometric Si3 N4 has been related to the cooling effect of large NH3 addition to the SiH4 warmed up in the laser absorption.